Kinetically simulation of photo-Fenton process in removal of sulfamethazine, ciprofloxacin, sulfathiazole and amoxicillin by Monte Carlo modeling - Dezhampanah, Hamid; Jalali, Hamed Moradmand (European Journal of Chemistry, 2022)
Kinetic Monte Carlo modeling was employed to investigate the kinetics and photodecomposition mechanism of sulfamethazine, ciprofloxacin, sulfathiazole, and amoxicillin antibiotics by the photo-Fenton process (iron(III) citrate/hydrogen peroxide in the presence of UV irradiation). The reaction kinetic mechanisms of each photo-Fenton degradation mentioned above have been achieved. The rate constants values for each step of the reaction mechanisms (including photo-Fenton process of antibiotics) were obtained as adjustable parameters by kinetic Monte Carlo simulation. The optimized values of iron(III) citrate and hydrogen peroxide were investigated through the obtaining the effect of their initial amounts on the rate of antibiotic elimination utilizing kinetic Monte Carlo simulation. The perfect agreement is observed between the simulation results and the experimental photo-Fenton data for the systems above.